Early reduction in gut microbiota diversity in critically ill patients is associated with mortality - Hannah Wozniak; Nadia Gaïa; Vladimir Lazarevic; Christophe Le Terrier; Tal Sarah Beckmann; Eleonora Balzani; Martin Urner; Jérôme Pugin; Jacques Schrenzel; Claudia-Paula Heidegger; Gut Microbiota working group (Annals of Intensive Care)
Abstract Background Critical illness is associated with an altered gut microbiota, yet its association with poor outcomes remains unclear. This study evaluates the early gut microbiota diversity changes in intensive care unit patients and its association with mortality. Additionally, it explores fecal pH as a potential biomarker for these changes. Methods In this prospective observational cohort study, fecal samples were collected at two time points: S1, the first stool passed upon intensive care unit admission, and S2, the first stool passed at least 24 h after S1. Full-length 16S rRNA gene sequencing was performed for gut microbiota analysis, with α-diversity measured using the Shannon index. Bayesian joint models were used to estimate the association between time-varying changes in gut microbiota diversity and 60-day mortality, as well as the association between daily changes in stool pH and in diversity. Results Twenty-four of 96 patients overall died during follow-up. Daily Shannon index decreased on average by −0.1 points [95% Credible Intervals (CrI) −0.20 to −0.10]. Every point decrease in Shannon index was associated with a 1.99-fold increase in the hazard of death (95% CrI, 1.04 to 4.51). Time-varying fecal pH levels were not associated with changes in Shannon index. Conclusions Gut microbiota diversity decreased over time, associated with increased mortality. Fecal pH is an unreliable marker of gut microbiota change. Future studies on gut microbiota and related biomarkers should focus on the initial days in the intensive care unit to detect and mitigate a decline in gut microbiota diversity.